Determination of Minerals in Kefir by Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES) - Ozcan, Tulay (Asian Journal of Chemistry, 2010)
The concentrations of the minerals, Ca, P, Na, K and Mg and the trace elements, Fe, Cu, Zn and Mn were determined in plain and flavoured kefir. The mean concentrations of minerals and trace elements were recorded in plain and flavoured samples: Ca, 1.28 ± 0.11; 1.11 ± 0.05, P, 8.71 ± 0.64; 8.02 ± 1.44, Na, 0.70 ± 0.15; 0.78 ± 0.20, K, 0.66 ± 0.30; 0.49 ± 0.30, Mg, 0.14 ± 0.02; 0.16 ± 0.05 as g/kg total solids and Zn, 6.82 ± 4.54; 6.35 ± 2.75, Fe, 3.38 ± 0.88; 3.71 ± 0.96, Cu, 1.10 ± 0.69; 1.22 ± 0.70, Mn, 0.02 ± 0.08; 0.38 ± 0.67 as mg/kg total solids, respectively. It was observed that trace element contents were higher in flavoured kefir samples than in plain kefir, probably due to the use of adjuncts.